Prosthetic Valve Endocarditis Caused by Pasteurella dagmatis, Germany - Felix A. Rottmann; Peter Schorle; Roland Giesen; Christoph Jäger (Emerging Infectious Diseases, 2024)
An 81-year-old male patient in Germany had prosthetic valve endocarditis caused by Pasteurella dagmatis after a domestic cat bite. We surgically treated a paravalvular abscess and administered definitive antibiotic therapy consisting of penicillin G and levofloxacin. The patient was discharged from the intensive care unit in good condition 21 days after the surgery.